Impact of information technology on SMEs survival rate in Malaysian manufacturing industry - Jamali, Mohammad Ali (2010)
This study focuses on the impact of information technology on the survival rate of small and medium enterprises (SMEs) in the manufacturing sector in Malaysia. It analyses the effects of information technology on survival of SMEs in 2000 and 2005, based on two separate groups of closed firms. The study attempts to present a rational relationship between theories of firm survival and information technology. It sets out to show that while factors such as minimum efficient size, market and firms attributes, transaction cost, uncertainty, opportunism, information asymmetry and atmosphere, profitability and learning have an impact on the survival of SMEs, the effect of information technology is also significant. The Cox Proportional Hazard Regression Model is used for estimation of coefficients and survival functions. Evidence suggests that factors such as minimum economies of scale, productivity, technology usage, profits, R&D, location and capital-labor ratio affect the survival of SMEs. Of equal importance is the expenditure on information technology, which is said to have an impact on the viability of firms. By employing the model this study presents that information technology expenditure has positive effect on survival of SMEs in Malaysian manufacturing sector in this period. The model further shows that information technology plays a bigger role among the larger SMEs than the smaller ones. Thus, policy maker with regard to main finding of this study should consider some policy for promoting the IT among SMEs, especially larger ones in Malaysian manufacturing sector. Moreover, for increasing survival of SMEs, policy maker should encourage R&D among SMEs and concentrate on some sector, which have high entry rate.